Local dealer adoption of a foreign manufacturer-sponsored internet-based information system (2010)
Firms often use Internet-based inter organizational information systems (IBIS) tofacilitate the integration of information and communication between channel members. However, in practice firms are sometimes reluctant or even refuse to adopt such systems, especially when sponsored by a foreign manufacturer to local dealers. This article presents an empirical study of 80 dealers faced with the IBIS decision from a large international tire manufacturer. The results indicate that perceived financial and usage benefits of the IBIS and security are important determinants of dealer adoption of an IBIS. Further, the results indicate that higher IBIS adoption levels correspond to changes in the nature of the channel relationship, operational and exchange benefits, and commitment of the dealer to the manufacturer.